Credo ateistico organizzato e libera comunicazione propagandistica degli orientamenti ideal-spirituali (Stato, Chiese e pluralismo confessionale, 2020)
Sommario: 1. Introduzione - 2. La dimensione della ‘non credenza’ e le direttive costituzionali - 3. Fenomeno ateistico collettivo, eguale libertà e pluralismo ideale - 4. Il libero esercizio della propaganda come strumento irrinunciabile di realizzazione della dimensione comunitaria della miscredenza.Organized atheistic belief and free propagandistic communication of the ideal-spiritual orientationsABSTRACT: With an its recent intervention, the Court of Cassation has clearly affirmed that the freedom of conscience of non-believers falls within the broader freedom, in religious matters, ensured by the articles 19 and 21 of the Constitutional Charter. A freedom to be understood also in the negative sense, having to exclude, within our system, any form of differentiation for the protection of the free, individual and collective, explanation both of religious faith and of atheism. In this order of ideas, any limits and prohibitions to the exercise of the right to propaganda of atheistic associations integrate the extremes of discrimination that are incompatible with the constitutional and supranational norms to guarantee the freedom of expression of thought, the ideal and confessional pluralism, the dignity of the human person and the neutrality of public authorities.